Mean Decrease in Distal Motor Latency after Treated with Local Steroid Injection in Symptomatic Patients of Carpal Tunnel Syndrome (Medical Forum Monthly, 2024)
Objective: To determine the mean decrease in distal motor latency after administration of local corticosteroid injection in symptomatic.Study Design: Quasi experimental trial study.Place and Duration of Study: This study was conducted at the Department of Neurology, Mayo Hospital, Lahore over a period of six months from 01.02.2012 to 31.07.2012.Materials and Methods: One hundred cases were included. Baseline distal motor latency (DML) was assessed by using nerve conduction study on distal position. Then patients were administered corticosteroid injection (triamcinolone acetonide 20mg) through distal (palmar) approach.Results: Mean age of the patients was 52.4±6.1 years. Out of 100 patients, 22 (22.0%) were males and 78 (78.0%) were females. Mean distal motor latency at baseline was 5.5±2.6, at 4th week 4.8±2.4 and mean decrease was observed 0.7±0.2.Conclusion: Local corticosteroid injection for carpal tunnel syndrome provides statistically significant mean decrease in distal motor latency on nerve conduction study in 4 weeks after injection.